Nicotinamide improves sevoflurane-induced cognitive impairment through suppression of inflammation and anti-apoptosis in rat - Wang, Ying (Int J Clin Exp Med, 2015)
Nicotinamide is amide form of vitamin B3, participate in oxidation-reduction reaction, and it plays an important role in the maintenance of normal life activities in cells; it has broad application prospects in the treatment of heart blood-vessel disease, respiratory disease, type 1 diabetes and inflammatory autoimmune diseases. Thus the present study aimed to identify whether the nicotinamide improves sevoflurane-induced cognitive impairment and its potential mechanisms in rat. Firstly, Male Sprague-Dawley rats were induced by 2.1% sevoflurane for 6 h. Protective function of nicotinamide on cognitive impairment was evaluated using Morris water maze test in the rats. Next, NF-κB and caspase-3 activities, and p53, Bax and Bcl-2 protein expression was executed using commercial kits and Western blot analysis, respectively. Preconditioning with nicotinamide could improve cognitive impairment in the rats. Administrate of nicotinamide suppressed the activation of NF-κB and caspase-3, reduced the protein expression of Bax, and promoted Bcl-2 protein expression in rats. The present results suggested nicotinamide improves sevoflurane-induced cognitive impairment and has an anti-inflammatory and anti-apoptotic effect against sevoflrane-induced damages.